Challenges Faced By Lab Technicians In Modern Healthcare Settings (Journal of Namibian Studies : History Politics Culture, 2022)
Lab technicians are integral to the functioning of modern healthcare systems, playing a pivotal role in conducting diagnostic tests and ensuring accurate patient care. However, they encounter various challenges that impact their efficiency and effectiveness in laboratory operations. This abstract explores the key challenges faced by lab technicians in contemporary healthcare settings, including high workload, rapid technological advancements, budget constraints, regulatory compliance, shortage of skilled personnel, workplace safety, interdisciplinary collaboration, and data management. Understanding and addressing these challenges are essential for optimizing laboratory services and improving patient outcomes.